2021
DOI: 10.1021/acs.jpcc.1c06780
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the CH3SSCH3–Au(111) System From Single Molecules To Full Surface Coverage: A Scanning Tunneling Microscopy Study

Abstract: The adsorption process of dimethyl disulfide onto the Au(111) surface was resolved with subnanometer resolution at temperatures below 130 K. We report two temperature dependent adsorption studies to reach totally different surface morphologies for this CH 3 SSCH 3 −Au(111) system. Starting with a coldsynthesis approach at low-temperature and low coverage, the STM images reveal preferential adsorption at specific regions on the Au(111) herringbone reconstructed surface. However, at saturated surface coverage, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…All the geometries were fully optimized to less than 0.5 meV energy convergence and less than 0.02 eV/Å forces. The choice of our DFT methodology, plane wave cutoff energies, and k-point was based on previous periodic DFT simulations of similar systems of type ,,, and size . VASP calculations were performed on species adsorbed to three-layer unreconstructed Au and on the same species in the gas phase.…”
Section: Methodsmentioning
confidence: 99%
“…All the geometries were fully optimized to less than 0.5 meV energy convergence and less than 0.02 eV/Å forces. The choice of our DFT methodology, plane wave cutoff energies, and k-point was based on previous periodic DFT simulations of similar systems of type ,,, and size . VASP calculations were performed on species adsorbed to three-layer unreconstructed Au and on the same species in the gas phase.…”
Section: Methodsmentioning
confidence: 99%
“…17 A first direct comparison between products of IET manipulation and photoexcitation revealed that the distance between the two products upon dimethyl disulfide dissociation on Au(111) is on average slightly shorter for 1.4 V excitation by electrons from the tip than for 254 nm (4.9 eV) excitation by an UV lamp. 18 It has been assigned to an excitation of higher electronic states by the photons, and thus an excess energy that leads to a motion of the photolytically dissociated molecules.…”
Section: ■ Introductionmentioning
confidence: 99%